Performance of the Party List Groups in the Philippines and the Public Trust (American Journal of Multidisciplinary Research and Innovation, 2023)
This study determines the strength of the relationship between the party list groups’ performance, projects and programs and public trust. Using survey questionnaires, the 120 randomly selected respondents from the towns of Pila, Sta. Cruz and Siniloan, province of Laguna, Philippines were asked about their level of awareness and satisfaction regarding the party list groups` performance, projects and program. .Frequency and percentage distribution, mean and Pearson correlation coefficient were used to analyze the data and information given by the respondents. It was found in this research that there is a positive correlation between the performance of the party list groups and the public trust. It is also manifested herein that there is a positive correlation between the projects and programs of the party list groups and the public trust. The respondents’ level of trust towards the party list groups is affected by the performance and implementation of the projects and programs of the latter. The more projects and programs are implemented in the communities, the higher is the public trust. If the respondents are satisfied with the efficient and timely delivery of goods and services, the incidence of public trust is high. After the data have been gathered and analyzed, the researcher recommends the following : 1) Build infrastructure projects like farm – to - market roads which will spur economic growth and therefore will create more awareness and trust in the rural areas; 2.) Implement more projects and programs in the far-flung areas like the upland barangays in Siniloan, Laguna 3) Intensify information dissemination program specially in the social media platforms like Facebook, Tiktok, Youtube and others to better inform the public on bills and resolutions filed by the party list groups in Congress.